Zakat distribution and programme for sustaining muallaf belief and thought - Johari F.; Ab. Aziz M.R.; Mohd Ali A.F.; Mohd Faisol Ibrahim (Penerbit UTM Press, 2024)
Zakat is one of the pillars of Islam that emphasises the socio-economic development. Any discussion on zakat in the context of worship cannot be disconnected from the socio-economic factor, especially in aiding the underprivileged. The primary purpose of zakat is to redistribute wealth of the society among the poor. Zakat is not purely welfare-oriented that relies on the contribution of the giver but an obligation that must be carried out to qualified recipients. Therefore, it is pertinent that the management of zakat is made efficient to ensure that the rights of the recipients and the society, in general, will not be put in jeopardy. The question is then raised regarding the type of zakat distribution or programmes pertaining to the asnaf Muallaf. The objective of this article is to explore zakat distribution programmes for sustaining muallaf belief (Tauhid) and thoughts (Iman). The methodology of this article is based on qualitative research through document analysis and interview with zakat officer. This article has revealed that a huge amount had been allocated for the development of asnaf Muallaf. It is conclude that, State Islamic Religious Council needs to continuously improve a comprehensive programmes that focus on sustaining the Muallaf belief (Tauhid) and thoughts (Iman). 2014 Penerbit UTM Press. All rights reserved.